Relación cultura - economía: Industrias culturales. (2021)
Culture and economics have been presented generally as separated areas and noticeable opposites. However, this article makes a brief approach in order to understand what cultural industries are, and aims as well to where artistic creation and economics match. Cultural activities jobs have an economical value; economical decisions are taken from cultural surroundings and vice versa; economical conditions affect the access to certain cultural practices; and not only from cultural industries the cultural practices are guaranteed and potecialised, but also symbolical processes owning are taken. The topic is viewed through a historical roundabout on theorical conceptualizations and political postures that have labeled the term oncoming, generating controversies and discussions.